Information and Communication Technology in Water Pollution Monitoring and Management - Choudhary, Vishal; Kumar, Vinit (Gyan Management Journal, 2007)
Now a day the major crisis faced by the world is the pollution of rivers. There are two solutions either we clean the water of rivers or to prevent the causes of pollution since first option is very costly so we could adopt the second option to control the pollution .in this paper we have presented the methods of monitoring and control mechanism for livers pollution. Our aim is to monitor rivers over the Internet. We can integrate state-of-the-art environmental monitoring with geographk information systems, data visualization. The goal of this paper is to provide realtime data to identify and resolve problems m water resource management. Water monitoring is based on a Remote Underwater Sampling Station consists of mobile underwater sensor package tethered to a floating platform containing an on-board computer, solar panels and telem
Keywords: Communication Technology; Water Pollution Monitoring; Management